2015
DOI: 10.1007/s13157-015-0632-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Elements in Waters and Sediments of Shallow Lakes: Relationships with Water, Sediment, and Watershed Characteristics

Abstract: We measured concentrations of multiple elements, including rare earth elements, in waters and sediments of 38 shallow lakes of varying turbidity and macrophyte cover in the Prairie Parkland (PP) and Laurentian Mixed Forest (LMF) provinces of Minnesota. PP shallow lakes had higher element concentrations in waters and sediments compared to LMF sites. Redundancy analysis indicated that a combination of site- and watershed-scale features explained a large proportion of among-lake variability in element concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 97 publications
(161 reference statements)
0
11
0
2
Order By: Relevance
“…Kissoon et al [42] have worked on shallow lakes in Minnesota, and they have suggested the extent to which multiple elements in shallow lake waters and sediments were influenced by a Tables 4 and 5). The extremely low calcium and magnesium content of the water of all ponds can be explained by the absence of any carbonate minerals in the bottom sediments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kissoon et al [42] have worked on shallow lakes in Minnesota, and they have suggested the extent to which multiple elements in shallow lake waters and sediments were influenced by a Tables 4 and 5). The extremely low calcium and magnesium content of the water of all ponds can be explained by the absence of any carbonate minerals in the bottom sediments.…”
Section: Discussionmentioning
confidence: 99%
“…The extremely low calcium and magnesium content of the water of all ponds can be explained by the absence of any carbonate minerals in the bottom sediments. Kissoon et al [42] have worked on shallow lakes in Minnesota, and they have suggested the extent to which multiple elements in shallow lake waters and sediments were influenced by a combination of variables, including sediment characteristics, lake morphology and percent of land cover in watersheds. These data may be informative for illustrating the extent of functional connectivity between shallow lakes and adjacent lands within these lake watersheds.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with Yellick et al (2016) for soils, we observed that the element composition of waters in a disturbed (grazed) wetland were different from undisturbed (natural) wetlands, most likely due to the deterioration of vegetation and soil. The surrounding landscape and land use practices can impact chemistry and element transfer in waters (Kissoon et al, 2015;Hummel, 2016), which lead to changes of element composition. Moreno-Mateos et al (2012) observed that biogeochemical functioning of restored wetlands was still lower than in reference wetlands even a century after restoration.…”
Section: Connectivity Between Wetlandsmentioning
confidence: 99%
“…Multi-element fingerprinting is based on quadrupole Inductively Coupled Plasma Mass Spectrometry (ICP-MS) analysis for determining the composition of influential chemical elements, and has been used for identification of water and sediment sources (Stutter et al, 2009;Rauch et al, 2010). The element composition (so-called multi-element fingerprint, see Markert et al, 2015) of soils and waters reflects the variation in biogeochemistry between wetlands in terms of environmental conditions such as hydrology, position in the landscape, and disturbances (Jacob et al, 2013;Kissoon et al, 2013Kissoon et al, , 2015Sullivan et al, 2014;Yellick et al, 2016). Knowledge about the element composition of wetland soils and waters is important for our understanding of their biogeochemistry, and for monitoring and restoration (Moreno-Mateos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation